Master's and doctoral theses in family medicine and their publication output, Suez Canal University, Egypt - Nour-Eldein, Hebatallah (J Family Med Prim Care, 2015)
BACKGROUND: The completion of a thesis is a significant requirement for both a Master's and a doctorate degree in general practice/family medicine (GP/FM). A postgraduate thesis is a well-planned, time-intensive activity carried out over several years. The quality of the theses can be judged by the proportion of published papers. OBJECTIVE: This study aimed to describe Master's and doctoral theses in family medicine and their publications between 1982 and 2014. MATERIALS AND METHODS: GP/FM degree theses were reviewed at the Faculty of Medicine and central Suez Canal libraries. Several characteristics were extracted from each thesis relating to the main researcher, supervisors, themes, and study methods according to predefined criteria. Publications from the theses were described. RESULTS: Over 33 years, 208 theses were completed by 173 GP/FM researchers. The majority of the theses were for Master's degrees (84.1%). Regarding the study design, most of the degree theses were cross-sectional studies (76.9%). The adult population was targeted in 33.7% of research theses. Nonprobability sampling was used in 51%. Rural communities were the setting of research in 43.8%, and primary health center (PHC)-based studies in 59.1%. The “Patient” category exceeded the other categories (28.4%). Publication from theses started in the second decade of research production. Of the degree theses, 21.6% original articles were published. Only 13.3% of articles from theses were published in PubMed-indexed journals. The researcher was first author in 62.2% of published articles. CONCLUSION: The production of GP/FM theses and their publications are going to increase. Continuous assessment and planning for GP/FM studies are recommended.